A study of knowledge and practice of contraception in a rural area of Bareilly, Uttar Pradesh - Saxena, Alpana; Gupta, S. B.; Singh, Atul K.; Singh, Meenakshi; Khan, Huma (International Journal Of Community Medicine And Public Health, 2021)
Background: It is very critical to understand that awareness of family planning and proper utilization of contraceptives is an important indicator for reducing maternal and neonatal mortality and morbidity. It also plays an important role in promoting reproductive health of the women in an underdeveloped country. Objective was to assess knowledge and practice of modern contraception in rural area. Methods: A community based cross sectional study. A cross-sectional descriptive study was carried out in the in a rural area of Bareilly, Uttar Pradesh. 458 randomly selected eligible couples were included in the study. A pre-structured questionnaire was used to collect information about family planning methods knowledge, source of knowledge and current practices and reasons of nonuse. The appropriate statistical analysis was done to present the results. Results: 48.03% eligible couples had adopted one or the other current modern contraceptive measure. Female sterilization was the most common method used. Conclusions: Overall usage of postpartum contraception was low need to focus at every step to contact with health facility or health workers.